Comparison of anxiety and pain in dental treatment of children by syringe with toy shape needle cover and conventional syringe - Majid Mehran; Roza Haghgoo; Mohsen Ashourioun; Elham Seifali; Nasrin Takzaree (Tehran University of Medical Sciences, 2019)
Background and Aims: Most children get a lot of anxiety while they visit a dentist. The most important factor in the child's fear at the beginning of treatment is the syringe and needle. Ways to cope with this anxiety include behavioural control techniques such as mental regeneration, distraction, and induction. The purpose of this study was to compare the pain and anxiety in children when using a syringe and toy- shape syringe needle. This study was the first study that used a toy-shape needle cover. Materials and Methods: This clinical trial study was conducted on 20 children age from 5 to 8 years. More than half of them were anxious with Cfss-Ds (Dental Subscale of the Children's Fear Survey Schedule) and FIS (Facial Image Scale) anxiety diagnostic tests, and the rest of them were not anxious. Patients were randomly divided into two groups. The first group received local anesthesia with conventional syringe and the second group, by syringe with toy shape needle cover. Following, the first group received local anesthesia by syringe with toy shape needle cover, and the second group, by a conventional syringe. Heart rate measuring and pain evaluating test was performed. Analysis of heart rate and anxiety data was performed by non-parametric wilcoxonsianed Ranks T-test (P-value was considered significant at 0.001). Results: The mean amount of pain measured after using a syringe with a toy shape needle cover and using conventional syringe had a significant difference of 5.20% between the two groups. The pain was reduced in children who received local anesthesia by syringe with toy shape needle cover (P<0.001). Conclusion: The physical appearance of the injection device plays an important role in reducing the anxiety and pain of injection in the children.